Diachrony and typology of non-finites in Indo-Aryan - Stroński, Krzysztof; Tokaj, Joanna; Jaworski, Rafał (Wydział Neofilologii, Uniwersytet im. Adama Mickiewicza w Poznaniu, 2020)
The present work provides a corpus-based analysis of various non-finite forms such as converbs, adverbial participles and infinitives appearing over the course of time in early New Indo-Aryan languages. It focuses on morphosyntactic properties of non-finites giving insights into the development of their forms and functions. To give a more detailed picture of the non-finite categories, main argument marking, control properties and scope of selected operators were analysed in order to trace the process of formation of clause linkage devices. The theoretical foundation was partly based on two models, i.e. Role and Reference Grammar and Multivariate Analysis. The corpus comprises early New Indo-Aryan texts from several dialectal groups, such as Early Rajasthani, Early Awadhi, Early Braj, Early Dakkhini and Early Pahari which were tagged by means of a newly developed tool IATagger.

Niniejsza praca zawiera analizę korpusową wybranych nieosobowych form czasownika, takich jak konwerby, imiesłowy przysłówkowe i bezokoliczniki pojawiające się w różnych fazach rozwojowych we wczesnych językach nowo indoaryjskich. Ponadto autorzy koncentrują się na właściwościach morfosyntaktycznych nieosobowych form czasownika, dając wgląd w rozwój różnych form i ich funkcji. Aby uzyskać bardziej szczegółowy obraz kategorii nieosobowych, przeanalizowano oznaczanie głównych argumentów zdaniowych, właściwości kontrolne i zakres wybranych operatorów w celu prześledzenia procesu tworzenia narzędzi zdaniotwórczych. Podstawę teoretyczną pracy stanowią częściowo dwa modele, tj. Gramatyce Roli i Referencji oraz Analiza Wielowymiarowa. Korpus zawiera wczesne teksty nowo indoaryjskie z kilku grup dialektalnych, takich jak wczesny radżastański, awadhi, bradź, dakkhini i pahari, które zostały otagowane za pomocą nowo opracowanego narzędzia IATagger.
Keywords: non-finites; Indo-Aryan; typology; historical morphosyntax; nieosobowe formy czasownika; języki indoaryjskie; typologia; morfoskładnia historyczna